2015
DOI: 10.18632/oncotarget.5621
|View full text |Cite
|
Sign up to set email alerts
|

Cancer metastasis and EGFR signaling is suppressed by amiodarone-induced versican V2

Abstract: Extracellular matrix components play an active role in cancer progression and prognosis. Versican, a large extracellular matrix proteoglycan, can promote cancer metastasis through facilitating cell proliferation, adhesion, migration and angiogenesis. We had previously demonstrated that amiodarone caused ectopic overexpression of similar to versican b (s-vcanb), inhibited EGFR/GSK3β/Snail signaling, and enhanced Cdh5 at the heart field of zebrafish, indicating interference with epithelial-mesenchymal transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
(48 reference statements)
2
18
0
Order By: Relevance
“…VCAN was the most up-regulated gene in SC. Of interest, VCAN has also been shown to interact with and influence EGFR signaling (50,51). VCAN is a major component of the extracellular matrix, being produced by both tumor cells and the surrounding stroma (52).…”
Section: Discussionmentioning
confidence: 99%
“…VCAN was the most up-regulated gene in SC. Of interest, VCAN has also been shown to interact with and influence EGFR signaling (50,51). VCAN is a major component of the extracellular matrix, being produced by both tumor cells and the surrounding stroma (52).…”
Section: Discussionmentioning
confidence: 99%
“…Lumican seems to be a potent inhibitor of EMT, as Wu et al () show that this SLRP is transcriptionally inhibited by HMGA2 and its expression is lost in high‐grade serous papillary carcinoma. A preventive role for hyalactan, versican 2, has been proposed in tumor cell lines, as up‐regulation of this PG leads to suppression of EMT‐related transcription factors' expressions through EGFR/Erk/GSK3‐β (Lee et al, ). Indeed, versican has been correlated with the opposite to EMT, the process of mesenchymal–epithelial transition (MET) (Soltermann et al, ; Gao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Amiodarone, a widely administered anti-arrhythmic drug [1], was shown by several pre-clinical studies to reverse multidrug resistance and sensitize several types of cancers to chemotherapy. Pre-clinical studies demonstrated its anti-cancer effects as a single therapeutic or in combination with other anti-cancer drugs on different cancers, including prostate, hepatocellular and breast carcinomas [6][7][8][9][24][25][26]. Based on this, we opted to investigate its anti-cancer effects on GBM, the most common and aggressive primary malignant brain tumor with a dismal prognosis outcome [13].…”
Section: Discussionmentioning
confidence: 99%